Scripts and information units in future planning: Interactions between a past and a future planning task - Cordonnier, Aline; Barnier, Amanda J.; Sutton, John (Quarterly Journal of Experimental Psychology, 2016)
Research on future thinking has emphasized how episodic details from memories are combined to create future thoughts, but has not yet examined the role of semantic scripts. In this study, participants recalled how they planned a past camping trip in Australia (past planning task) and imagined how they would plan a future camping trip (future planning task), set either in a familiar (Australia) or an unfamiliar (Antarctica) context. Transcripts were segmented into information units that were coded according to semantic category (e.g., where, when, transport, material, actions). Results revealed a strong interaction between tasks and their presentation order. Starting with the past planning task constrained the future planning task when the context was familiar. Participants generated no new information when the future camping trip was set in Australia and completed second (after the past planning task). Conversely, starting with the future planning task facilitated the past planning task. Participants recalled more information units of their past plan when the past planning task was completed second (after the future planning task). These results shed new light on the role of scripts in past and future thinking and on how past and future thinking processes interact.